In Vitro Digestibility Evaluation Ammoniated Palm Frond as Cattle Feed - Andayani, Jul; Sadarman, Sadarman; Novianti, Sri; Kaswari, Teja; Fatati, Fatati; Qomariyah, Novia; Sastrawan, Sandri; Prihambodo, Tri Rachmanto (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
This study aimed to assess the potential of ammonia-treated palm fronds as a substitute for conventional forage in animal feed through in vitro analysis. The materials used were palm fronds, elephant grass, fine bran, corn, coconut meal, and urea. This study employed a Completely Randomized Design (CRD) with five treatments and four replications. The treatments applied in this study were: T0: 70% forage (all grass, no ammoniated palm fronds) + 30% concentrate, T1: 70% forage (75% grass, 25% ammoniated palm fronds) + 30% concentrate, T2: 70% forage (equal portions of grass and ammoniated palm fronds) + 30% concentrate, T3: 70% forage (25% grass, 75% ammoniated palm fronds) + 30% concentrate, and T4: 70% forage (entirely ammoniated palm fronds, no grass) + 30% concentrate. The observed variables in this study encompassed pH, digestibility of dry matter, organic matter, and crude protein, as well as the digestibility of NDF, ADF, and hemicellulose. The data obtained in this experiment were analyzed using analysis of variance (ANOVA) according to the design used. The post hoc test used was Duncan's multiple range test. The experimental results indicated that the treatments did not significantly affect (P>0.05) pH after in vitro testing. However, they had a significant impact (P<0.05) on the digestibility of dry matter, organic matter, crude protein, NDF, ADF, and hemicellulose. Digestibility increased with the increasing percentage of ammoniated palm fronds in the diet. In conclusion, this research demonstrates that the ammoniation process can improve the quality of palm fronds, leading to increased digestibility of palm fronds in the diet. Ammoniated palm fronds can replace forage in cattle feed based on nutrient digestibility in vitro.